Sosialisasi Intervensi Anak yang Lahir dan Tumbuh dengan Stunting : Pemberian MP-Asi pada Anak Usia 6-24 Bulan - Devitasari, Ivana; Widia, Lidia; Kasanova, Evy (Compromise Journal Community Proffesional Service Journal, 2024)
Interventions for children born and raised with stunting can be recaptured before 2 years of age. Giving complementary food at the right time with good and correct processing of complementary food will help maximize child growth and development so as to reduce the risk of stunting. Community service is carried out on baby mothers at Posyandu Melati, participants in community service totaled 10 people with community service methods namely lectures, questions and answers, discussions, and demonstrations. All community service participants know when to give complementary food to children and how to process complementary food correctly. This community service is important to reduce the incidence of stunting by one of the most important ways is to provide nutritious nutrition for children by giving complementary food optimally.